(untitled) (Research, Society and Development, 2022)
Objective: Explore the nature of evidence supporting the effects antidepressants based on previous scientific studies that showed satisfactory results. Methodology: It consists of an integrative review focused on analyzing articles published between 2016 and 2022 found in virtual databases: LILACS, PubMed, SciELO and Science Direct using the descriptors: “ayahuasca, ayahuasca depression, ayahuasca pharmacology. Banisteriopsis caapi, Psychotria viridis”. Results: In the initial search period were found resulted in 1.402 articles, with 106 publications potentially eligible according to the inclusion and exclusion criteria adopted, after reading the abstracts, 37 remained and of those only 4 were chosen to compose the analysis corpus. It is possible to conclude that the use of ayahuasca in patients with depression showed effective results, that is ayahuasca can be a considerable resource of plant origin to help fight this disease. Further studies are still needed to be carried out with tea.